Long-Distance Romantic Relationships among International Students: “My First Qualitative Research” - Fenny Rizky Amelia (Studies in Philosophy of Science and Education, 2020)
The purpose of this study was to seek depth information how international students maintain their relationship to stay feeling close with their romantic partners although separated by distance or live in a different country, the difficulties and the reasons they choose to remain in the long-distance relationship. Semi-structured interviewed were conducted to four international students. Five themes emerged, they are “keep in touch”, “this is my look”, “trustworthiness as foundation”, “family’s support”, and “relationship’s goal is get married”. The participants utilize many ways of communication to keep in touch well because it also becomes a difficulty for the relationship if it is not done seriously. Since many of the participants have got support from their family, it makes them more believed that this relationship would be no matter even in a long-distance relationship. Admittedly, the distance has both beneficial and negative aspects, but how the couples handle it through the communication, always trust each other and share the relationship’s goal, determined the maintenance and help to feel close in the long-distance relationship.